2014
DOI: 10.1542/peds.2013-4223
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea and Sickle Cell Anemia

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Obstructive sleep apnea syndrome (OSAS) prevalence in children with sickle cell anemia is not well described. Although these children often experience nocturnal oxygen desaturation, it is unclear whether they are more likely to have OSAS.WHAT THIS STUDY ADDS: Children with sickle cell anemia have a high prevalence of OSAS with typical symptoms, beyond just nocturnal oxyhemoglobin desaturation. This study supports the need for increased efforts to screen for, diagnose, and treat OS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
132
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(141 citation statements)
references
References 56 publications
(28 reference statements)
3
132
0
Order By: Relevance
“…Nonetheless, when detected, nocturnal oxygen desaturation should be viewed as a surrogate marker for a more severe disease, and those patients should be referred for more comprehensive evaluation. Nocturnal SpO 2 values also correlate with [25,36], as well as with a diagnosis of OSA [37], thus emphasizing the importance of evaluating daytime oxygen saturation during any routine clinic visit, and potentially performing a standardized exercise test designed for that specific purpose.…”
Section: Nocturnal Hypoxemiamentioning
confidence: 99%
“…Nonetheless, when detected, nocturnal oxygen desaturation should be viewed as a surrogate marker for a more severe disease, and those patients should be referred for more comprehensive evaluation. Nocturnal SpO 2 values also correlate with [25,36], as well as with a diagnosis of OSA [37], thus emphasizing the importance of evaluating daytime oxygen saturation during any routine clinic visit, and potentially performing a standardized exercise test designed for that specific purpose.…”
Section: Nocturnal Hypoxemiamentioning
confidence: 99%
“…This obstructive sleep apnea may play an important role in the previously described neurocognitive dysfunction seen in SCD patients. 26 Direct imaging and quantitative assessment of the lymphoid tissue is rarely performed; however, the findings of lymphoidal hypertrophy are frequently identifiable on routine imaging of the brain, spine, or neck (See Fig. 18).…”
Section: Lymphoid Tissuementioning
confidence: 99%
“…SCA were retrieved after thorough literature search (Table 1A-1C) [4,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. We categorized these articles in 3 groups according to the criteria used to define NE.…”
Section: Introductionmentioning
confidence: 99%
“…Group 3 (Table 1c): These are the studies that used different diagnostic criteria, they reported a prevalence rate of 32.2%-68.9% [4,[16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%